Cobalt (II) complexes of Diamino Diamide in Aqueous Solution - Majhi, G.; Bhattamisra, S.D. (Asian Journal of Chemistry, 2010)
An investigation of the interaction of Co(II) with N,N'-bis-(β-carbamoylethyl) ethylenediamine (BCAN) has been carried out. The stability constants as well as the distribution of solution complexes have been determined by analytical potentiometry in 0.1 M KNO3 at 30°C. Electronic spectra of different complex species of the ligand have been measured in aqueous solution under similar conditions. Based on the bond rearrangement at the amide sites as well as the deprotonation of amide protons, the structures of the Co(ll) complexes have been discussed.